2015
DOI: 10.1073/pnas.1421200112
|View full text |Cite
|
Sign up to set email alerts
|

GABA-mediated repulsive coupling between circadian clock neurons in the SCN encodes seasonal time

Abstract: The mammalian suprachiasmatic nucleus (SCN) forms not only the master circadian clock but also a seasonal clock. This neural network of ∼10,000 circadian oscillators encodes season-dependent day-length changes through a largely unknown mechanism. We show that region-intrinsic changes in the SCN fine-tune the degree of network synchrony and reorganize the phase relationship among circadian oscillators to represent day length. We measure oscillations of the clock gene Bmal1, at single-cell and regional levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
229
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(251 citation statements)
references
References 54 publications
13
229
3
Order By: Relevance
“…It has been shown that excitatory GABA action drives reentrainment of the shell region in response to light phase shifts (17). GABA action was examined in depth in recent collaborative works (16,26); these studies demonstrated the encoding of day length through the GABA pathway, by the Cl − -dependent excitatory (core, phase-attractive) or inhibitory (shell, phase-repulsive) effects of slow-scale (tonic) GABA. Visually, the core regions identified in our networks overlap with the regions of excitatory GABA action (26).…”
Section: B Amentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that excitatory GABA action drives reentrainment of the shell region in response to light phase shifts (17). GABA action was examined in depth in recent collaborative works (16,26); these studies demonstrated the encoding of day length through the GABA pathway, by the Cl − -dependent excitatory (core, phase-attractive) or inhibitory (shell, phase-repulsive) effects of slow-scale (tonic) GABA. Visually, the core regions identified in our networks overlap with the regions of excitatory GABA action (26).…”
Section: B Amentioning
confidence: 99%
“…GABA action was examined in depth in recent collaborative works (16,26); these studies demonstrated the encoding of day length through the GABA pathway, by the Cl − -dependent excitatory (core, phase-attractive) or inhibitory (shell, phase-repulsive) effects of slow-scale (tonic) GABA. Visually, the core regions identified in our networks overlap with the regions of excitatory GABA action (26). In future studies, our TTX-based assay could be combined with VIP/GABA/glutamate agonist or antagonist application and repeated to identify the molecular mechanisms responsible for the identified connections.…”
Section: B Amentioning
confidence: 99%
See 3 more Smart Citations